PENGARUH CASH FLOW, ACCOUNT RECEIVABLE TURNOVER, MODAL KERJA DAN PERTUMBUHAN PENJUALAN TERHADAP LIKUIDITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nina Andriany Nasution; Armalita Oktari (Jurnal Akuntansi Bisnis dan Publik, 2021)
The purpose of this study was to determine the effect of Cash Flow on Liquidity, to determine the effect of Account Receivable Turnover on Liquidity, to determine the effect of Working Capital on Liquidity and to determine the effect of Sales Growth on Liquidity in Manufacturing companies listed on the IDX 2016-2019 Period. The population in this study were all manufacturing companies listed on the IDX as many as 173 companies and samples from the study were 56 companies with 4 years of observation totaling 192 samples. The data collection technique used in this research is documentation. The analysis technique used in this research is descriptive statistics, Multiple Linear Regression Analysis, and the Determinant Coefficient Test. The results showed that Cash Flow, Account Receivable Turnover, Working Capital, Sales Growth together had a significant and significant effect on Liquidity in Manufacturing Companies Listed on the IDX for the 2016-2019 period. Partially Cash Flow has a positive and significant effect on Liquidity, Account Receivable Turnover partially has a negative an insignificant effect on Liquidity, Working Capital partially has a positive and significant effect on Liquidity, and Sales Growth partially has a negative and insignificant effect on Liquidity in the company Manufacturers listed on the IDX for the 2016-2019 period. The coefficient of determination test results with the R Square value of 0.421 or 42.1% of the liquidity variable can be explained by Cash Flow, Account Receivable Turnover, Working Capital, and Sales Growth, while the remaining 57.9% is from other variables not examined. by this research.